2018
DOI: 10.1371/journal.pone.0206261
|View full text |Cite
|
Sign up to set email alerts
|

Increased Trimethylation of histone H3K36 associates with biliary differentiation and predicts poor prognosis in resectable hepatocellular carcinoma

Abstract: IntroductionTrimethylation of histone H3K36 (H3K36me3), an epigenetic marker of transcription-associated histone modification and stem cell regulation, is expressed in a variety of human cancers. This study elucidated the prognostic significance of H3K36me3 in patients with resectable hepatocellular carcinoma (HCC).MethodsExpression of H3K36me3 was retrospectively evaluated through immunohistochemistry in 152 surgically resected primary HCCs.ResultsIn nontumorous liver parenchyma, H3K36Me3 was detected in bile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Histone modification is one of the epigenetic changes that regulate the chromatin structure and, therefore, impact diverse DNA-templated procedures [4]. Accumulating studies have demonstrated that changes in histone modification occurred in different types of human malignant tumours and having value in clinical practice, such as markers for predicting prognosis, assessing therapeutic response to some chemotherapeutic drugs, and emerging therapeutic targets for treating cancers [5][6][7]. There are five histone families in human, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Histone modification is one of the epigenetic changes that regulate the chromatin structure and, therefore, impact diverse DNA-templated procedures [4]. Accumulating studies have demonstrated that changes in histone modification occurred in different types of human malignant tumours and having value in clinical practice, such as markers for predicting prognosis, assessing therapeutic response to some chemotherapeutic drugs, and emerging therapeutic targets for treating cancers [5][6][7]. There are five histone families in human, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…H3K36me3 was shown to have the highest degree of epigenetic modification hubs that were altered by NO exposure. H3K36me3 was also found to be associated with a poor prognosis in hepatocellular carcinoma (60) and corelated with cancer-related gene expression in cancer cell lines (61). In addition, H3K79Me3 is one of the histone modifications of interest due to controlling epithelial-to-mesenchymal (EMT) (62) and the stemness of certain cells (63).…”
Section: Discussionmentioning
confidence: 99%
“…H3K36, which refers to lysine 36 from the N-terminus of histone H3, is associated with actively transcribed genes, especially when it undergoes tri-methylation (H3K36me3) [60]. H3K36me3 is thought to function in DNA mismatch repair, modulation of chromatin structure, and stem cell regulation [60]. SETD2 is the only methyltransferase thought to tri-methylate H3K36 in the literature [66].…”
Section: H3k36me3mentioning
confidence: 99%
“…Interestingly, similar to the prognostic significance of H3K27me3, H3K36me3 expression levels have been correlated with both better or worse survival in different cancer types. Lien et al demonstrated that in HCC, H3K36me3 positivity on immunostaining is not only a predictor of high tumor grade and stage, but is also a contributor to tumor recurrence and poor survival [60]. In contrast, Ho et al discovered that even when adjusting for age and a validated prognostic scoring, loss of H3K36me3 expression was associated with higher risk of renal cell carcinoma-specific death and progression after nephrectomy in clear cell renal cell carcinoma patients [61].…”
Section: H3k36me3mentioning
confidence: 99%